Do Social Networks Increase Labour Supply Elasticity? - Yueh, L (2008)
Using an original data set including measures of social networks of migrants in China, we find that social networks increase the elasticities of labour supplies for migrant workers. The effects differ for men and women and can help explain part of the importance of developing social networks to improve labour market outcomes.